1964
DOI: 10.1037/h0042496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of positive social reinforcement on regressed crawling of a nursery school child.

Abstract: Use of social reinforcement procedures to help a child substitute already established walking behavior for recently reacquired crawling behavior was studied in a nursery school situation. Adult attention was systematically given as an immediate consequence of one behavior and withheld as an immediate consequence of the other behavior. Results indicated that (a) adult attention had powerful reinforcement values; (b) reversal of reinforcement procedures had distinct positive effects; and (c) systematic use of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(33 citation statements)
references
References 4 publications
0
33
0
Order By: Relevance
“…It yielded six publications; we included four of them. These were Allen, Hart, Buell, Harris, and Wolf's (1964) report of reducing isolate play and increasing social play; Harris, Johnston, Kelley, and Wolf's (1964) report of reducing ''regressed'' crawling; B. M. Hart, Allen, Buell, Harris, and Wolf's (1964) report of reducing operant crying and increasing appropriate verbal behavior; and M. K. Johnston, Kelley, Harris, and Wolf's (1966) report of increasing gross motor play and walking. We excluded Baer (1964, 1967) because they were identical reviews of this research.…”
Section: The Early Applied Behavioral Research Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It yielded six publications; we included four of them. These were Allen, Hart, Buell, Harris, and Wolf's (1964) report of reducing isolate play and increasing social play; Harris, Johnston, Kelley, and Wolf's (1964) report of reducing ''regressed'' crawling; B. M. Hart, Allen, Buell, Harris, and Wolf's (1964) report of reducing operant crying and increasing appropriate verbal behavior; and M. K. Johnston, Kelley, Harris, and Wolf's (1966) report of increasing gross motor play and walking. We excluded Baer (1964, 1967) because they were identical reviews of this research.…”
Section: The Early Applied Behavioral Research Literaturementioning
confidence: 99%
“…If, again, founding means first, then Ayllon's was the field's founding program. Its first publication was in 1959 (Ayllon & Michael, 1959), whereas Wolf's was in 1964 (Harris, Johnston, Kelley, & Wolf, 1964). However, if we had included Baer et al's (1968) behavioral dimension among our inclusion criteria, then Wolf's would have been the founding program.…”
Section: Independent Assessmentsmentioning
confidence: 99%
“…When Ayllon moved to Anna State Hospital in Illinois in 1961, he collaborated with Azrin in related research (e.g., Ayllon & Azrin, 1964, the best known of which was on the token economy (Ayllon & Azrin, 1968), now considered "a landmark in the development of applied behavior analysis" (Kazdin, 1978, p. 260;see Kazdin, 1977). Wolf et al (1963Wolf et al ( -1967 Wolf Harris, & Wolf, 1966), and walking (F. R. Harris, Johnston, Kelley, & Wolf, 1964), and decreased operant crying . This work has been referred to as the "most influential application of operant techniques with children" (Kazdin, 1978, p. 264), and its evolving applied research methods have been described as "groundbreaking" (Risley, 2005, p. 280).…”
Section: The Emergence Of Applied Behavior Analysis: 1959-1967mentioning
confidence: 99%
“…The application of operant conditioning to this behavior was the first applied behavior analysis in autism (see Wolf, Risley, & Mees, 1964; see also Wolf, Risley, Johnston, Harris, & Allen, 1967). 2 Wolf also conducted research with the Institute's nursery school teachers on children's classroom problem behavior and the role of teacher attention in shaping and maintaining it (e.g., Harris, Johnston, Kelly, & Wolf, 1964). At the CDC, Robert C. Wahler analyzed how parents contributed to their children's asocial behavior and showed that mothers could serve as their therapists (Wahler, Winkel, Peterson, & Morrison, 1965), and Robert P. Hawkins independently conducted research on home-based parent training (Hawkins, Peterson, Schweid, & Bijou, 1966).…”
Section: Back At Washingtonmentioning
confidence: 99%